Glycerol Monolaurate Affects Growth, Amino Acid Profile, Antioxidant Capacity, Nutrient Apparent Digestibility, and Histological Morphology of Hepatopancreas in Juvenile Pacific White Shrimp (Litopenaeus vannamei) - Sami Ullah; Bingge Liu; Yunyun Zheng; Hongbo Guo; Yarui Yang; Muhammad Ijaz Ahmad; Siyu Lv; Shijie Deng; Minjie Zhao; Fengqin Feng (Fishes, 2025)
An eight-week feeding trial was conducted to evaluate the effects of dietary supplementation with glycerol monolaurate (GML) on Pacific white shrimp (Litopenaeus vannamei). A basal diet was formulated containing 100 g fish meal, while four additional GML-supplemented diets were prepared: GML1 (0.25 g), GML2 (0.50 g), GML3 (0.75 g), and GML4 (1.00 g). Each diet was given to triplicate tanks containing 50 shrimp, each weighing 1.67 ± 0.25 g. GML2 supplementation enhanced the final body weight, weight gain, condition factor, specific growth rate, and viscerosomatic index of the shrimp compared to the other diets (p